Implementasi Manajemen Pengetahuan dalam Sistem Layanan Sertifikasi Profesi (Studi Kasus SMKN 1 Garut) - Andriansyah Maulana; Christina Juliane (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Professional certification body (LSP) P1 SMKN 1 Garut as the executor of competency test activities in SMKN 1 Garut and in SMKN network LSP P1 SMKN 1 Garut LSP. LSP P1 SMKN 1 Garut requires a knowledge management model that will be implemented during the skill competency certification process. This study aims to design a knowledge management model from knowledge capture to knowledge application which is expected to help improve the effective and efficient performance of the professional certification process at LSP P1 SMKN 1 Garut. A knowledge management model can increase the collaboration of knowledge owned by parties involved in the professional certification process, which is expected to continue to develop knowledge and provide an effective and efficient performance impact on the professional certification process. With the design of a knowledge management model in the certification system at LSP P1 SMKN 1 Garut, it will make it easier to store knowledge because a knowledge management system is a virtual repository for relevant information which is very important for tasks carried out by parties related to the professional certification process in Indonesia. LSP P1 SMKN 1 Garut.